Financing Muslim Education in India: Prospects for Islamic Finance - Ali, Saad (İstanbul Sabahattin Zaim Üniversitesi, 2024)
Education financing is an important item of Fiscal Budget of every nation. Every nation is endeavoring to achieve high literacy rate. The World Bank Report on Education has suggested that there is direct relationship between level of education and level of pay. The annual economic and social cost of illiteracy for India is estimated to be $ 53.56 Billion. Many steps have been taken to educate every citizen of India such as The Right to Education Act 2009 etc., yet the India’s aim of universal education is still a dream. India houses 37% of global illiterates. With this, the state of Muslim literacy (68.54%) is far below the national average (72.98%). The major Muslim literates are concentrated in below primary and primary education. If we do not consider the below primary level as level of education, the revised illiteracy rate among Indian Muslims stands at 52.07%. One the other hand, the Islamic schools cover a very small section of Muslim children. The official data says only 4% Muslims, in their age of schooling, attend Islamic schools. Such a low rate of educational attainment with high drop-out rate is inspired by various factors. One major factor is lack of sufficient resources and inadequate education financing options with Muslims of India. Further, considering the unique Islamic view of education, the existing educational resources are insufficient to meet the education needs of Muslims. This study aims to identify and analyze existing financing modes and financing sources of Muslim education institutions in India. An effort has been made to explore new mode as an alternate mode of financing of Muslim education. For this purpose, the study covers a wide range of topics related to state of Muslims in education, and existing financing patterns of Muslim education. The theme of chapter one revolves around Muslims in India and their education. Chapter two analyses the education resource availability to Muslims and their existing modes of financing education. The last chapter explores some new models of financing education that are feasible in the present Indian legal and financial framework. A blend of qualitative and quantitative analysis of data and information has been used to reach at the conclusions. The quantitative analysis is intentionally kept simple to make this study useful to large users. The Population Census-2021 has been further postponed until the 2024 national elections, so the latest population data related to the size of Muslim population, the literacy rate etc., is not available. Hence, Census 2011 is generally referred, and various other primary references have been deployed to make the study more up to date. Various previous studies have been considered during the present study. It is important to note that, except for a few, no studies have analyzed the existing financing patterns of Muslim education in India. For the sufficiency of data, the analysis of financial statements of Muslim education institutions, conduct of semi-structured survey, etc., have been used for collection of relevant information. The study concludes that the Muslim education resource requirements and the actual resource availability with modes of financing are greatly at odds. There is a need to identify some alternate modes of financing for Muslim Education. Islamic finance can do good as there exists an observable gulf between the Indian financial system and Muslim participation. Considering the India’s target of an all-inclusive growth and a five trillion US Dollar economy, the size of Muslim population and the Indo-Arab trade relations justify the introduction of Islamic finance in India.

Eğitim finansmanı her ulusun Mali Bütçesinin önemli bir kalemidir. Her ulus yüksek okuryazarlık oranına ulaşmak için çabalıyor. Eğitim düzeyi ile ücret düzeyi arasında doğrudan bir ilişki olduğu ileri sürülmüştür. Okuma yazma bilmemenin Hindistan'a yıllık ekonomik ve sosyal maliyeti 53,56 Milyar Dolar. Hindistan'ın her vatandaşını eğitmek için Eğitim Hakkı Yasası, 2009 gibi pek çok adım atıldı, ancak Hindistan'ın evrensel eğitim hedefi hâlâ bir hayal. Hindistan küresel okuma yazma bilmeyenlerin %37'sine ev sahipliği yapıyor. Ayrıca Müslüman okur-yazarlık durumu (%68,54) ulusal ortalamanın (%72,98) çok altındadır. Eğitimli Müslümanların çoğunluğu ilkokul ve ilköğretimin altında yoğunlaşmıştır. Eğitim düzeyi olarak yalnızca ilköğretim altı düzeyini dikkate almazsak, Hintli Müslümanlar arasında revize edilen okuma yazma bilmeme oranı %52,07'dir. Bir diğer yandan, İslami okullar Müslüman çocukların çok küçük bir bölümünü kapsamaktadır. Resmi veriler, eğitim çağındaki Müslümanların yalnızca %4'ünün İslami okullara gittiğini söylüyor. Eğitime katılım oranının bu kadar düşük olması ve okuldan ayrılma oranının yüksek olması çeşitli faktörlerden kaynaklanmaktadır. Önemli faktörlerden biri, Hindistan Müslümanları için yeterli kaynak eksikliği ve yetersiz eğitim finansmanı seçenekleridir. Daha öte, İslam'ın kendine özgü eğitim anlayışı göz önüne alındığında, mevcut eğitim kaynakları Müslümanların eğitim ihtiyaçlarını karşılamada yetersiz kalmaktadır. Bu çalışma, mevcut Müslüman eğitim kurumlarının nasıl finanse edildiğini tespit etmeyi ve analiz etmeyi amaçlamaktadır. Müslüman eğitiminin alternatif bir finansmanı olarak her türlü yeni yöntemin araştırılması için çaba sarf edilmiştir. Bu amaç için, Çalışma, Müslümanların eğitimdeki durumu ve Müslüman eğitiminin mevcut finansman modelleri ile ilgili geniş bir yelpazedeki konuları kapsıyor. Birinci bölümün teması Hindistan'daki Müslümanlar ve onların eğitimi etrafında dönüyor. İkinci Bölüm, Müslümanların eğitim kaynaklarının kullanılabilirliğini ve mevcut eğitim finansman şekillerini analiz etmektedir. Son olarak üçüncü bölüm, Hindistan'ın mevcut yasal ve mali çerçevesinde mümkün olan bazı yeni eğitim finansmanı modellerini araştırıyor. Sonuçlara ulaşmak için veri ve bilgilerin niteliksel ve niceliksel analizinin bir karışımı kullanılmıştır. Bu çalışmayı büyük kullanıcılar için faydalı kılmak amacıyla niceliksel analiz kasıtlı olarak basit tutulmuştur. 2021 Nüfus Sayımı 2024 genel seçimlerine kadar ertelendi, Dolayısıyla, Müslüman nüfusun büyüklüğü, okuma-yazma oranı ile ilgili en son nüfus verileri mevcut değil. Genel olarak 2011 Nüfus Sayımı'na atıfta bulunulmuştur ve çalışmayı daha güncel hale getirmek için çeşitli diğer birincil referanslar kullanılmıştır. Bu çalışma sırasında daha önce yapılan çeşitli çalışmalar dikkate alınmıştır. Şunu vurgulamakta yarar var, birkaçı hariç, Hindistan'da Müslüman eğitiminin mevcut finansman modellerini analiz eden hiçbir çalışma yok. Verilerin yeterliliği için Müslüman eğitim kurumlarının mali tablolarının analizi, yarı yapılandırılmış anket yapılması vb. yöntemlerden yararlanılmıştır. Çalışma, Müslüman eğitim kaynak gereksinimleri ile finansman modları ile gerçek kaynak mevcudiyetinin büyük ölçüde çelişkili olduğu sonucuna varıyor. Müslüman Eğitimi için bazı alternatif finansman türlerinin belirlenmesine ihtiyaç vardır.
Hindistan'da Müslümanların Eğitiminin Finansmanı: İslami Finans İçin Beklentiler
Keywords: Muslim Education In India; Educational Resource Availability; Existing Modes Of Financing Education; New Education Financing Options; Islamic Finance In India; Hindistan'da Müslüman Eğitimi; Eğitim Kaynağı Kullanılabilirliği; Eğitimin Mevcut Finansman Şekilleri; Yeni Eğitim Finansmanı Seçenekleri; Hindistan'da İslami Finans